Terrorism as Security Policy Issue - Bulatović, Aleksandra (Zbornik Instituta za kriminološka i sociološka istraživanja, 2015)
Contemporary theoretical approaches to security, by and large, depict terrorism as a phenomenon best comprehended by using descriptive methodologies, via studying terrorist groups, and by analysing the motivation of particular terrorist groups, and models of response to their actions. Parallely, the core value of war-making against the terrorism model remains unresolved. Although terrorism appears fundamentally the same in its every instance, perception of terrorism defines reaction, and political factors determine its weight. The principle embedded in the idea that violence against civilians cannot be rewarded with political concessions stands as one of the deeply rooted values of Western civilisation. However, the experience generates the conclusion that the stance "there could be no negotiations with terrorists" is not viable, given that it does not diminish the terrorist threat but, quite the contrary, facilitates the expansion of terrorism to new territories in every sense of the word. The author provides arguments in the article in support of the conclusion that the results of the "war against terror", as consequences of exclusive repression and non-negotiation, point towards the necessity to critically re-examine the standard repressive approach as a reaction to terrorism.